Akutes Leberversagen - Koch, A. (Med Klin Intensivmed Notfmed, 2017)
Acute liver failure (ALF) is a rare, but life-threatening disease that is characterized by the acute onset of jaundice, coagulopathy, and hepatic encephalopathy (HE) in patients without pre-existing liver disease. Main causes in Germany are drug toxicity, acetaminophen overdose, and viral hepatitis (A, B, E). For the initial assessment of patients with ALF and the diagnostic algorithm, the early detection of HE, exclusion of liver cirrhosis, immediate diagnosis of the underlying etiology, and evaluation for the necessity of liver transplantation (LT) are critical. Intensive care therapeutic measures aim at preventing or treating complications of ALF. Potentially, plasmapheresis (full plasma exchange) offers a survival benefit for ALF patients who do not undergo LT. The King’s College criteria and the Clichy criteria are used as prognostic tools for the indication for LT.